TIPE INTERVAL T2- HUMMOCKY PADA ENDAPAN BADAI (TEMPESTIT), FORMASI NANGGULAN, PEGUNUNGAN KULON PROGO, YOGYAKARTA - Nuraini, siti; Syafri, Ildrem; Muljana, Budi; Sudradjat , Adjat (KURVATEK, 2025)
The composition of storm deposit layers (tempestites) is described as a normal sedimentary deposit or fining upward-deposit, divided into 3 units: the lower part, the middle part, and the upper part. The lower part is characterized by coarse clastics, the middle part known as T2 consists of a combination of hummocky and swalley layers containing finer clastics with good sorting. The upper part shows deposition of layering in increasingly calm current conditions with fine clastics: clay. The T2 interval is often considered a characteristic of turbidite deposit models due to gravity flow. However, on the other hand, the nature of storm-induced currents (hummocky-swalley) is more varied due to the role of 3 controlling currents: oscillatory currents, bottom currents, and combined currents. This study will investigate the characteristics of storm interval T2 (tempestites) in the Nanggulan Formation. The method applied is to generate stratigraphic sections for 3 sections (Kali Clumprit, Watupuru, and Songgo), age correlation and of paleocurrents analysis. Storm deposits are found in the Middle Eocene-aged Nanggulan Formation, showing a polymodal direction with opposing and branching within T2 interval. This pattern reflects two opposing directions: bottom currents and storm oscillatory currents. On the other hand, a combination current emerges, branching off from the main current pattern. The T2 Watupuru layer consists of overlapping hummocky layers that extend in a northwestward direction, indicating an ancient coastal or land area.